Prognostic significance of hematological parameters and albumin in BCMA-targeted CAR-T therapy for multiple myeloma - Jiang, Liansheng; Ren, Hefei; Ke, Zhiqing; Liu, Yaoting; Liu, Chang; Zhou, Lin (Frontiers in Immunology, 2025)
Multiple myeloma is an incurable hematologic malignancy, and CAR-T therapy can benefit some patients with relapsed or refractory disease. However, due to individual variations, treatment outcomes vary significantly among different patients. We retrospectively analyzed 77 relapsed/refractory MM patients receiving BCMA-targeted CAR-T therapy. Baseline and dynamic hematological/nutritional parameters were assessed at four time points: prior to CAR-T cell collection, before pre-lymphodepletion therapy, before CAR-T cell infusion, and within the 7-day post-infusion. Prognostic groups were stratified by progression-free survival (PFS ≤ 10 vs. > 10 months). The results demonstrate that patients in the poor prognosis group consistently exhibited significantly lower levels of HGB, RBC, and HCT throughout the treatment period(p<0.05). Before pre-lymphodepletion ALB level in the poor prognosis group was significantly lower than that in the good prognosis group (p<0.05). LDH, creatinine, calcium ions, and β2-microglobulin showed no differences at the four observation time points(p>0.05). ROC analysis confirmed prognostic value for HGB (AUC = 0.693), RBC (AUC = 0.669), HCT (AUC = 0.691), and ALB (AUC = 0.756) (all p < 0.05). Kaplan-Meier analysis linked low HGB (≤92.5 g/L), RBC (≤3.26 ×10¹²/L), HCT (≤32.05%), and ALB (≤35.3 g/L) to inferior PFS (p = 0.011, 0.014, 0.0033, and 0.0001, respectively). Low ALB (≤35.3 g/L) before pre-lymphodepletion is a practical biomarker for risk stratification, reflecting compromised bone marrow reserve and immune-nutritional status. These accessible parameters may optimize patient selection and supportive care strategies.